PHYTOCHEMICAL SCREENING OF VOLVARIELLA VOLVACEA (STRAW MUSHROOM) EXTRACT FROM ACEH’S LOCAL CULTIVATION - Sadli . (Jurnal Natural, 2018)
Abstract. A research on analyzing the phytochemical content in Volvariella volvacea (straw mushroom) extract from a local cultivation in Aceh has been conducted. Straw mushroom is potentially a medicine ingredient. This study aims to examine the secondary metabolite compounds in the methanol extract of straw mushroom. The extraction of the secondary metabolite compounds was undertaken by using the maceration method with methanol solvent. Phytochemical test was conducted qualitatively by using the meyer’s reagent, bouchardat, dragendrof, FeCl3, HCl 0.1 M, HCl 2N and Lieberman – bouchardat. Phytochemical analysis was carried out on flavonoids, alkaloids, glycosides, saponins, tannins and terpenoids. The phytochemical analysis’ result shows that the straw mushroom extract contains alkaloids, flavonoids, terpenoids, and saponins.Keywords: straw mushroom, methanol extract, maceration method, phytochemical screening